The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.15171/jcs.2018.019
|View full text |Cite
|
Sign up to set email alerts
|

Effective Clinical Teaching Behaviors Views of Nursing Students and Nurse Educators at University of Gondar, Northwest Ethiopia: Cross-Sectional Institution Based Study

Abstract: Introduction: Clinical teaching behavior is a critical determinant for quality of clinical learning. Nursing students’ and instructor’s perception of effective clinical teaching behavior (ECTB) is important to modify and facilitate clinical education. Thus, the main purpose of this study was to assess the effective clinical teaching behavior (ECTB) as perceived by students and nursing instructors. Methods: Facility based cross-sectional descriptive study design was conducted among 178 participants. Data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 24 publications
(28 reference statements)
2
34
0
Order By: Relevance
“…While the lack of research exploring the relationship between core practice competencies and teaching efficacy limits further discussion, based on our results, we assume that those with high core practice competency have a greater likelihood of demonstrating high teaching efficacy. The work of Bifftu et al (2018) reports that while students rate teaching ability as the most important clinical teaching attribute for efficacy, instructors have been shown to rate nursing competency as the most important clinical teaching attributes for efficacy. Further studies are needed to validate the relationship between practice competencies and teaching efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the lack of research exploring the relationship between core practice competencies and teaching efficacy limits further discussion, based on our results, we assume that those with high core practice competency have a greater likelihood of demonstrating high teaching efficacy. The work of Bifftu et al (2018) reports that while students rate teaching ability as the most important clinical teaching attribute for efficacy, instructors have been shown to rate nursing competency as the most important clinical teaching attributes for efficacy. Further studies are needed to validate the relationship between practice competencies and teaching efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of clinical education in nursing programmes is crucial for meeting student learning outcomes and leading students to success (Oermann, 1998). A well‐structured clinical education has tremendous influence on the cultivation of students’ decision‐making, critical thinking, clinical reasoning and skills, ability to communicate, theoretical knowledge, interpersonal skills and attitude towards the nursing profession (Bifftu et al, 2018; Niederriter et al, 2017). Ultimately, effective clinical education stands to contribute to better patient safety and quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…The study findings were consistent with other studies such as Bifftu et al study in Ethiopia, which found that the majority of students reported personality traits and teaching abilities as the most effective clinical instructors' behaviors. The majority of faculty members reported interpersonal relations and nursing competence as the most effective behaviors (Bifftu et al, 2018). In the Philippines, Soriano and Aquino found that the majority of the students selected personality traits and interpersonal relations as the most effective behaviors, and faculty members selected nursing competence and teaching abilities as the most effective ones (Soriano & Aquino, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, this claim is contradicted, the presence of an instructor made the students anxious and felt like being examined (Msiska, Smith & Fawcett, 2014). Teachers' competence is the most influential factor in students' clinical learning (Bifftu, Dachew, Tiruneh, Ashenafie, Tegegne &Worku, 2018;Ludin & Fathullah, 2016). However, when the instructors had inadequate clinical experience, the students could not learn effectively in the clinical area (Jahanpour, Azodi, Azodi & Khansir, 2016).…”
Section: Effective Characteristic Of Clinical Teachermentioning
confidence: 99%